Hubungan Dukungan Orang Tua Dengan Prestasi Futsal Putri di SMKN 1 Cianjur ( Penelitian Dalam Kegiatan Ektrakulikuler ) - Arief Adhitia Hamzah; Ai Faridah; Acep Ruswan; Dian Permana; Bela Santika; Satrio Damar Panuluh (Edukasi Elita : Jurnal Inovasi Pendidikan, 2024)
The purpose of this study aims to determine the effect of parental support on achievement in women's futsal extracurricular activities at SMKN 1 Cianjur. This research is an ex post facto. The study population was the female futsal extracurricular of SMKN 1 Cianjur, totaling 10 players. The sampling technique used purposive sampling, with the criteria (1) willing to be a sample, (2) aged 16-18 years, (3) have participated in matches, (4) still actively practicing. Based on these criteria, there were 10 people who met. The instrument of parental support for women's futsal achievement using a questionnaire. Data analysis using Correlation Product Moment. Parental support has an important role for every child, including as a role model, motivator and initiator. In other words, parents as a family have a hand in every achievement obtained by a child. Achievement is an action that makes someone do the desired thing. Someone who wants to be recognized in their environment needs recognition from those around them.